Thinking Africa through Soga"s black spirituals: A theological reflection - Kobe, Sandiswa L. (HTS teologiese studies, 2024)
This article offers a critical reflection of Lizal’isidinga laKho (hymn 116) and Wazidala iinto zonke (hymn 16) written by Tiyo Soga and recorded in the Methodist Church of Southern Africa (MCSA) hymnal book. From the perspective of black theology of liberation (BTL), I historicise and contextualise hymn 116 and hymn 16 to debunk the argument that Tiyo Soga was alien to the lives, experiences of suffering and pain of his people. The article posits that hymn 116 and hymn 16 are black spirituals that articulate the contexts Soga found himself as a black person during the times of the frontier wars. Therefore, utilising blackness as a heuristic approach, I argue that the songs do not just historicise the experiences of black people in the times of the frontier wars, but they are prayers and/or laments from Soga that ask God to spare the lives, the culture, and value systems of black people in a world that seeks the destruction of their being, history, and culture. The songs emphasise the black struggle for justice and liberation encouraging black people never to succumb to the definitions given to them by those who seek the destruction of black personhood. The article locates Soga within the frontier wars to illustrate his own experiences as black person, then examines and presents Lizal’isidinga laKho, Wazidala iinto zonke as black spirituals born in a time of war to give hope to those who have been conquered and subjugated in the unjust wars of colonisation. Hymns 116 and 16 contribute to the decolonial turn discourse –unthinking of the west – because they emphasise the black struggle for liberation and justice.Contribution: The contribution of this article is its focus on the way in which the intersection of religious studies, social sciences, and humanities generates an interdisciplinary contested discourse.